(untitled) (The Pakistan Development Review, 2003)
This paper looks into the interrelation between economic growth, inequality, and poverty. Using the notion of pro-poor growth, we examine the extent to which the poor benefit from economic growth. First, various approaches to defining and measuring propoor growth are scrutinised using a variety of criteria. It is argued that the satisfaction of a monotonicity axiom is a key criterion for measuring pro-poor growth. The monotonicity axiom sets out a condition that the proportional reduction in poverty is a monotonically increasing function of the pro-poor growth measure. The paper proposes a pro-poor growth measure that satisfies the monotonicity criterion. This measure is called a ‘poverty equivalent growth rate’, which takes into account both the magnitude of growth and how the benefits of growth are distributed to the poor and the non-poor. As the new measure satisfies the criterion of monotonicity, it is indicative that to achieve rapid poverty reduction, the poverty equivalent growth rate—rather than the actual growth rate—ought to be maximised. The methodology developed in the paper is then applied to three Asian countries, namely, the Republic of Korea, Thailand, and Vietnam.